نمط الشخصية وعلاقته باستجابة القلق لدى عينة من أساتذة التعليم الابتدائي حسب تصنيف كارل يونغ. - أسماء بركات دنيا شبلي, • فايزة دحماني (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2021)
تهدف الدّراسة الحالية إلى الكشف عن طبيعة العلاقة بين نمط الشخصية واستجابة القلق لدى أساتذة التعليم الابتدائي، ولتحقيق أهداف الدّراسة تّم تطبيق مقياس ايزنك ترجمة احمد محمد عبد الخالق سنة 1991 ومقياس القلق لتايلور ترجمة كل من مصطفى فهمي ومحمد احمد غالي على عيّنة قوامها (30) أستاذ وأستاذة من أساتذة الابتدائي بولاية المسيلة، وتم التوصل إلى النّتائج التّالية: 1. توجد علاقة ارتباطية ذات دلالة إحصائية بين نمط الشخصية الانبساطي حسب كارل يونغ واستجابة القلق لدى أفراد عينة الدراسة. 2. توجد علاقة ارتباطية ذات دلالة إحصائية بين نمط الشخصية الانطوائي حسب كارل يونغ واستجابة القلق لدى أفراد عينة الدراسة. 3. لا توجد فروق ذات دلالة احصائية في مستوى القلق لدى أفراد عينة الدراسة تعزى لمتغير الجنس (ذكر، أنثى). 4. لا توجد فروق ذات دلالة احصائية في مستوى القلق لدى أفراد عينة الدراسة تعزى لمتغير الاقدمية. 5. لا توجد فروق ذات دلالة احصائية في مستوى القلق لدى أفراد عينة الدراسة تعزى لمتغير السن. The current study aims to reveal the nature of the relationship between personality pattern and anxiety response among primary school teachers, and to achieve the objectives of the study, the Eisenk scale was applied to translate Ahmed Mohamed Abdel Khaleq in 1991 and the anxiety measure for Taylor translated by Mustafa Fahmyand Mohamed Ahmed Ghali on a sample of (30) professors and professors of primary teachers in The State of M'sila, and the following results were reached: 1. There is a statistically significant correlation between the diastolic personality pattern, according to Carl Young, and the anxiety response of the study sample members. 2. There is a statistically significant correlation between the introverted personality pattern, according to Carl Young, and the anxiety response of the study sample members. 3. There are no statistically significant differences in the level of anxiety in the study sample members attributable to the sex changer (male, female). 4. There are no statistically significant differences in the level of anxiety among the study sample members due to the age change. 5. There are no statistically significant differences in the level of anxiety among the study sample members due to the age changer.